0510 Parent and Child Perception of Sleep for Children with Sensory Processing Difficulties. (25th May 2022) - Hartman, Amy; Soehner, Adriane; Smagula, Stephen; McKendry, Sarah; Bendixen, Roxanna
Abstract: Introduction: Roughly 5.3 million elementary children in the United States experience sensory processing (SP) difficulties, like sensitivity to touch and overstimulation with movement. These difficulties cause high levels of daytime stress and daytime dysfunction (e.g., difficulties with attention, academics, and emotional regulation). In typically developing children (without SP difficulties), high levels of daytime stress impact sleep; however, research has yet to explore sleep health in children with SP difficulties. Our study aims to use validated self- and parent-reported questionnaires to characterize differences in sleep health for children with and without SP difficulties. Methods: Children (ages 6-10) with (n=22) and without (n=33) SP difficulties (per parent report; Autism and ADHD diagnosis excluded) were recruited for this convergent mixed-methods study. Sleep was assessed using validated self- and parent-report questionnaires, the Sleep Self-Report (SSR) and Children's Sleep Habits Questionnaire (CSHQ), and through qualitative interviews with parents. Groups were compared using t-test and Mann-Whitney U tests, with significance set a priori at α=0.05. A rapid qualitative analysis produced themes and were integrated with the quantitative data. Results: Parents of children with SP report significantly worse sleep quality on the CSHQ difficulties (MedianSP= 50.5, SDSP= 11.45) than parents of children without SP difficulties (MedianCON=43.0, SDCON=7.27, U= -2.92, p=.004). Children with SP deficits also report significantly worse sleep on the SSR (MSPD=42.18, SDSPD=8.26) compared to their peers (MCON=33.55, SDCON=6.71, t(53)= -4.26, p<.001). Qualitative themes highlight the higher prevalence of rigid, lengthy bedtime routines and adaptations within the sleep environment (e.g. specific pajamas, special bedding) to support sleep for children with SP difficulties. Parents of children with SP difficulties also report higher frequencies of an adult being in the room while the child falls asleep and co-sleeping in the middle of the night. Conclusion: Parents and children both report poorer sleep in children with SP difficulties when compared to peers. Future studies should incorporate other sleep health measurement tools (e.g. actigraphy) to further understand areas to target for intervention. Support (If Any): Sensory Integration Education Network PhD Grant (PI: Hartman, 2021); University of Pittsburgh's School of Health and Rehabilitation Science's PhD Student Award (PI: Hartman, 2021).